Learning and inclusion in space of non-formal education: experience report - Perussi Vasconcellos, Talita Silva [UNESP]; Orlando, Rosimeire Maria (Univ Nove Julho, 2021)
This experience report seeks to present an experience of socio-educational inclusion carried out in a non-formal teaching environment through the project methodology. The experience aimed to elaborate, develop and exhibit a project about China, striving to work on its multiple potentials. It was characterized as a case study, of a qualitative nature, and used the project methodology for its realization. It took place for a semester at a Civil Society Organization in the interior of Sao Paulo that assists girls, children and adolescents in vulnerable situations. Girls between 8 and 12 years old were selected, among them, one with Cerebral Palsy. Based on the interest of the participants, during the meetings, each group researched a certain curiosity about the mentioned country. Throughout the process, the participants had opportunities to make choices about their interest in the subject. The experience was enriching for all, including the girl with Cerebral Palsy who participated throughout the course.
Keywords: special education; non-formal education; cerebral palsy; project methodology